In vivo Pharmacokinetic and Pharmacodynamic (PK/PD) Modeling and Establishment of the PK/PD Cutoff of Florfenicol Against Pasteurella multocida in Ducks - Xiao, Xia; Lan, Weixuan; Zhao, Yaqin; Li, Ruichao; Liu, Yuan; Liu, Juan; Wang, Zhiqiang (Frontiers in Microbiology, 2021)
Pasteurella multocida can invade and translocate through endothelial cells and result in vascular-system infection, which can cause severe economic losses in the poultry industry. Antibacterial therapy (especially florfenicol) plays an important part in controlling P. multocida infection. To preserve the effect of florfenicol, in vivo pharmacokinetic/pharmacodynamic (PK/PD) modeling of florfenicol against three P. multocida strains in duck was established. Then, the efficacy of the currently marketed dose, a rational dosage regimen for populations, and the PK/PD cutoff were predicted through Monte Carlo simulations (MCSs). The area under the concentration–time curve from 0 h to 24 h/minimum inhibitory concentration (AUC0–24 h/MIC) was the optimal PK/PD parameter. The PK/PD surrogate values of florfenicol against P. multocida were similar using different organs as the PD target, but varied in different strains. For the florfenicol-sensitive strain 0825Y1, when the AUC0–24 h/MIC reached 117.54 and 108.19, florfenicol showed a bactericidal effect in the liver and lung, respectively. For the florfenicol-sensitive strain 0901J1, the corresponding value was 78.39 and 54.30 respectively. For the florfenicol-resistant strain JY160110, florfenicol could attain a maximum effect of 1 − log10 reduction in bacteria in the liver and lung when the AUC0–24 h/MIC reached 2.03 and 2.06, respectively. The PK/PD-based prediction for the population dose indicated a poor effect for the low end of the currently marketed dose (40 mg/kg bodyweight per day), but a robust effect for the high end of the currently marketed dose (60 mg/kg bodyweight per day) with a target attainment rate of 92.79% and 81.44% against P. multocida in mainland China and worldwide, respectively. The recommended dose optimized by MCSs was 52 mg/kg bodyweight in mainland China. The PK/PD cutoff of florfenicol against P. multocida at the low end and high end of the current daily dose (40, 60 mg/kg bodyweight) and predicted daily dose in mainland China (52 mg/kg bodyweight) was 0.25, 4 and 0.5 μg/mL, respectively. These results suggested that more than one strain should be involved for PK/PD modeling and contributed to rational use of florfenicol in populations. We also provided fundamental data for determination of florfenicol breakpoints in poultry.